The Legal Assistance of Eligible Age for Marriage in Law Number 16 of 2019 as an Effort to Prevent Child Marriage - Ahmad Mukhlisin; Iwannudin Iwannudin (Bulletin of Community Engagement, 2022)
Marriage must be in accordance with the provisions in force in the marriage law, In order to obtain legal protection. As the regulations regarding the limit marriageable age either men or women with a minimum of 19 years old, as stated in Law No. 16 of 2016. This rule was substituted for the rules that contained in Law Number 1 of 1974, which states that age minimum marry was 16 years. This article provided understanding to the community about the Eligible Age to prevent child marriage through Legal Assistance. The researchers used Community Based Research (CBR). The sample was 50 participants, especially for under 18 years old. for This assistance was carried out in the form of training with resource persons from legal experts. The result showed that the participants was more comprehensive about the latest regulation of Law Number 16 Number 2019 that stated the minimum for married women was 19 years old. The participants was quite successful, cause increased understanding of community about the importance of prevention of early marriage. Keywords: Legal Assistance Marriage, Legal Children Marriage, Prevent Child Marriage